On the Brink of-Noun vs. On the Verge of-Noun: a Distinctive-Collexeme Analysis - Wiliński, Jarosław (Research in Language, 2017)
This paper uses the terminology of Construction Grammar (Goldberg 1996; 2006) and a corpus-based method to investigate a pair of semantically similar constructions and the lexemes that occur in both of them. The method, referred to as distinctive-collexeme analysis (Gries and Stefanowitsch 2004a), seeks to identify lexemes that exhibit a strong preference for one construction as opposed to another: in other words, to uncover subtle distributional differences between two semantically or functionally near-equivalent constructions. On the basis of the case study dealing with the on the brink of- noun construction versus the on the verge of- noun construction, the paper shows that there are lexemes that prefer one of the investigated patterns over the other. Moreover, the results of the distinctive-collexeme analysis reveal that the frame-constructional semantics is a relevant factor in the choice between these two patterns.